Risk–Return Efficiency of Stochastic Oscillator Strategies in BRICS During COVID-19 and Geopolitical Conflicts - Poonam; Malik, N. S. (Indian Journal of Finance, 2025)
Purpose : This study examined the risk–return efficiency of stochastic oscillator-based trading strategies in BRICS stock markets during the COVID-19 pandemic and recent geopolitical conflicts. Methodology : Using daily index data from January 2018 to May 2025, the study applied t-tests, CAGR, alpha ratio, and Sharpe ratio to assess the performance of the stock market. Findings : The stochastic oscillator failed to outperform the buy-hold strategy consistently. Positive results were limited to Russia and South Africa, while Brazil, India, and China showed weak or negative risk-adjusted returns. Practical Implications : Traders in BRICS markets used stochastic strategies cautiously, especially in volatile environments, and avoided relying on them as standalone tools. Originality : This research added to the literature by uniquely analyzing the stochastic oscillator under crisis conditions, offering practical insights for active trading in emerging markets.